Not all is COVID19: a case of eclampsia and posterior reversible encephalopathy syndrome in the emergency room. - Poggiali, Erika; Morelli, Nicola; Terracciano, Chiara; Minervino, Guglielmo; Contardi, Emanuela; Zaino, Domenica; Vercelli, Andrea; Magnacavallo, Andrea (Acta Biomedica Atenei Parmensis, 2021)
In the so called COVID19 era, headache, fever and gastrointestinal symptoms are highly suggestive for SARS-CoV-2 infection, but in all the cases presenting to the emergency room, clinicians should always keep in mind alternative diagnoses, particularly if the patient is pregnant.  Life-threatening diseases, such as eclampsia and posterior reversible encephalopathy syndrome (PRES), should be promptly recognized and treated. Eclampsia is defined as a seizure occurring in association with pre-eclampsia, and it represents one of the major and serious obstetric disorders associated with significant maternal and perinatal morbidity and mortality. PRES is a distinctive clinical and imaging syndrome characterized by acute headaches, visual impairment, seizures, and altered sensorium, that can be associated with severe eclampsia. Emergency clinicians should always consider eclampsia in the differential diagnosis of headache in pregnant women. The prompt and accurate diagnosis of eclampsia/PRES is crucial to prevent adverse maternal and perinatal outcomes. Here we describe the case of a young pregnant woman admitted to our emergency department for fever, dyspnea, headache, nausea and vomiting, who developed generalized tonic clonic seizures and a subsequent status epilepticus due to eclampsia and PRES.